2004
DOI: 10.1258/00236770460734407
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a forced-air warming system to traditional thermal support for rodent microenvironments

Abstract: Thermal homeostasis is important for the well-being of laboratory rodents during experimental investigations involving chemical restraint. Anaesthesia-induced hypothermia may alter physiological processes, prolong recovery times, or result in death. Therefore, active warming may be needed to prevent excess heat loss from the rodent to the environment. Three methods of active warming were evaluated in typical rodent procedural areas and recovery cages: a forced-air warming system, infra-red heat emitter and cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…In a recent publication of Rembert et al (2004) it was clearly shown that the postoperative recovery of mice takes twice as long in a room with 18 8C ambient temperature compared to mice operated in a room with 26 8C. The ambient temperature in the animal facilities for the present study was 20.0 F 0.5 8C and it has to be taken into consideration whether a slightly increased ambient temperature would have an additional positive influence on the perioperative normothermia for the experimental animals in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent publication of Rembert et al (2004) it was clearly shown that the postoperative recovery of mice takes twice as long in a room with 18 8C ambient temperature compared to mice operated in a room with 26 8C. The ambient temperature in the animal facilities for the present study was 20.0 F 0.5 8C and it has to be taken into consideration whether a slightly increased ambient temperature would have an additional positive influence on the perioperative normothermia for the experimental animals in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Domitor is a sedative which acts through an alpha-2-receptor antagonistic pathway with analgesic and muscle relaxing characteristics. The use of a 2 -sedatives can impair the function of central thermoregulatory centers (Rembert et al, 2004). Thus, the anesthetic schedule (kind of anesthetics and time point of application) should have a major impact on the choice of the adequate warming system and temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia of small rodents is particularly challenging mainly due to hypothermia, high metabolic rate and the lack of reliable clinical signs of respiratory and cardiovascular functions (Rembert et al, 2004), highlighting the importance of pre-anesthetic evaluation. This evaluation entails a thorough clinical assessment of the animal and precedes the delivery of anesthetic care for surgery.…”
Section: Pre-anesthetic Evaluationmentioning
confidence: 99%
“…It is well-known that the thermoregulatory mechanisms in mice are suppressed during general anaesthesia [13]. This, in combination with their high body surface-to-mass ratio, makes them very susceptible to hypothermia and their temperature often drops by several degrees Celsius within a few minutes of the onset of anaesthesia [2, 4].…”
Section: Introductionmentioning
confidence: 99%